Phytochemical Analysis and Antibacterial Activity of Nicotiana tabacum and Nicotiana rustica - Muhammad Tariq (Jinnah University for Women, 2021)
Background: All over the world, natural products containing different secondary metabolites have been used for antibacterial purposes, and as folk medicines with significant effects. Amongst many different plants, Tobacco plants are cultivated all over the world, but natively belong to America. These plants contain variety of secondary metabolites and possess significant antibacterial activity.